ANALISIS PREFERENSI KONSUMEN ANTARA MINYAK GORENG KEMASAN DAN CURAH DI PASAR BASAH MALL MANDONGA KOTA KENDARI - Irmansyah S., Darlis; Bahari, Bahari; Rianse, Ilma Sarimustaqiyma (Fakultas Pertanian Universitas Halu Oleo, 2023)
This study aims to determine consumer preferences between packaged and bulk cooking oil at the Mandonga Mall Wet Market, Kendari City. The determination of the research area was carried out purposively with the consideration that one of the largest markets in Kendari City is the Mandonga Mall Wet Market which is located on Jalan Lasandara, Korumba Village, Mandonga District, Kendari City. The number of samples in this study, for packaged cooking oil was 35 samples and bulk cooking oil was also 35 samples, so that the total number was 70 samples. Data analysis uses Chi Square analysis and Multiatribut Fishbein. The cooking oil that is consumer preference based on the consumer attitude index towards price attributes is packaged cooking oil with a consumer attitude index value of 18,43.